1996
DOI: 10.1111/j.1432-1033.1996.0720u.x
|View full text |Cite
|
Sign up to set email alerts
|

Separate Compartments for the Production of Sterols, Carotenoids and Gibberellins in Gibberella fujikuroi

Abstract: Substrate flows in the sterol, carotenoid and gibberellin pathways of Gibberella ,fujikuroi were examined by isotope-dilution experiments. The wild type and two carotenoid mutants of this fungus were grown in minimal medium with abundant glucose, limiting ammonium nitrate and a radioactively labelled precursor (either acetate, mevalonate or leucine). The precursors did not affect growth or terpenoid production, with two exceptions ; leucine allowed additional growth, as expected from the nitrogen limitation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 27 publications
2
34
0
Order By: Relevance
“…Similar feeding experiments performed with Gibberella fujikuroi, indicated that such a compartmentation also occurred in this fungus for the formation of ergosterol, carotenoids and gibberellins [7]. Such radiolabeling experiments, however, even if they were in accordance with the role of MVA as precursor, do not exclude the participation of other possible pathways to IPP.…”
Section: Isoprenoid Biosynthesis Via the Mva Pathway Inmentioning
confidence: 77%
See 2 more Smart Citations
“…Similar feeding experiments performed with Gibberella fujikuroi, indicated that such a compartmentation also occurred in this fungus for the formation of ergosterol, carotenoids and gibberellins [7]. Such radiolabeling experiments, however, even if they were in accordance with the role of MVA as precursor, do not exclude the participation of other possible pathways to IPP.…”
Section: Isoprenoid Biosynthesis Via the Mva Pathway Inmentioning
confidence: 77%
“…This suggested that they were all issued from a single acetyl-CoA pool. The di¡erences observed in the incorporation of radiolabeled acetate, MVA or leucine into di¡er-ent isoprenoid series of Phycomyces blakesleeanus and Gibberella fujikuroi [6,7] actually re£ected the compartmentation of the MVA pathway in the fungal cells and were therefore most probably not related to the presence of two di¡erent routes to IPP as observed in higher plants. …”
Section: Isoprenoid Biosynthesis Via the Mva Pathway Inmentioning
confidence: 94%
See 1 more Smart Citation
“…This is followed by the synthesis of isopentenyl diphosphate (IPP) and several condensation steps, the latter mediated by a prenyl transferase presumably shared by both pathways and encoded by fppS (23), to yield farnesyl diphosphate (FPP). From this point, separate specific enzymes, encoded by genes ggs1 (31) and gibA (originally ggs2 [45]), are used to produce the common precursor geranylgeranyl diphosphate (GGPP) in different subcellular locations (15). The biosynthesis of gibberellins depends on seven genes organized in a cluster (44).…”
mentioning
confidence: 99%
“…3). This implies that the biosyntheses of the three groups ofterpenoids are physically separated in subcellular compartments (Domenech et al, 1996). Similar experiments indicated that the biosyntheses of carotenes and sterols are physically separated and independently regulated in the fungus Phycomyces blakesleeanus (Bejarano & Cerda-Olmedo, 1992).…”
Section: Relation Between Gibberellin Carotenoid and Sterol Biosynmentioning
confidence: 56%